Water and electrolyte losses and replenishment in children during prolonged exercise in the heat: Physiological and perceptual considerations - Meyer, Flavia (My University, 1993)
Recommendations regarding fluid replenishment for children who exercise are scarce and based on adult data. The objectives of this thesis were to evaluate and identify factors that would help optimize fluid replenishment for children who exercise in a warm environment. Total sweat electrolyte losses were compared among maturational groups (males and females) exercising in the heat (chapters 2 and 3). Total sweat Na⁺ and Cl⁻ losses, even when corrected for body weight, were greater in young men and women compared to their prepubescent and pubescent counterparts. Children and adults lost similar amounts of K⁺, lactate, and ammonia per kg body weight. Within the same maturational group, there were no gender differences in any of these electrolyte losses. Chapter 4 summarizes the effect of hypohydration (induced by exercise in the heat) on thirst, drink preferences, and the subsequent voluntary rehydration. Thirst and drink preferences were assessed while children dehydrated up to 0.8% of their initial body weight in four separate trials (one flavored drink in each). Thirst intensity increased during dehydration. Grape was the preferred drink during the entire dehydration phase, but its desirability did not increase as much as it did with the orange, apple and water drinks. This is possibly due to a ceiling effect. During recovery, most subjects rehydrated with all drinks, exceeding baseline levels by 0.40% (apple) to 0.76% (grape). The magnitude of overhydration, however, was greater with grape and orange than with water and apple. Chapter 5 summarizes the effect of ingesting various electrolyte drinks on thermoregulation and performance of children who were kept euhydrated while exercising in the heat. Four grape-flavored drinks were tested. One drink was water and the other three had 6% carbohydrate (4% sucrose, 2% fructose) with different [Na⁺] (0, 8.8, 18.5 mmol∙1⁻¹). Rectal temperature, heart rate and performance were similar among trials. A negative Na⁺ deficit occurred with all drinks but in a greater extent with Na⁺-free drinks. Na⁺ intake did not modify plasma [Na⁺] or osmolality. Drink composition had no effect on thirst and stomach fullness sensations, nor did it affect voluntary intake during recovery. The main conclusions of this thesis were: (1) Adults lost more Na⁺ and Cl⁻ from sweat than children. (2) Children's thirst intensity and drink preferences increased in response to minimal dehydration levels. (3) Grape was the most desirable drink. (4) Children spontaneously overhydrated following hypohydration induced by exercise. (5) Compared to water, CHO-electrolyte drinks had no effect on thermoregulation, performance, and perceptual responses of children who were kept euhydrated while exercising in the heat.
Keywords: Pharmacology; Physiology; Pharmacology